Efeito da densidade de criação e do sexo sobre o empenamento, incidência de lesões na carcaça e qualidade da carne de peito de frangos de corte - Garcia, R. G. [UNESP]; Mendes, A. A. [UNESP]; Garcia, E. A. [UNESP]; Nääs, I. A. [UNESP]; Moreira, J. [UNESP]; Almeida, I. C.L. [UNESP]; Takita, T. S. [UNESP] (My University, 2002)
The experiment was conducted at the College of Veterinary Medicine and Animal Production of UNESP-Botucatu Campus to evaluate the effect of stocking densities and sex on body injuries and breast meat quality. One thousand nine hundred and fifty day-old Ross chicks were reared until 42 days of age on a randomized factorial arrangement with three stock densities (10, 13 and 16 birds/m2) and two sexes. At 28, 35 and 42 days of age, 15 birds/treatment were sampled to determine feathering percentage related to body weight and 50 birds/treatment to evaluate score feathering. At 42 days of age, all broilers were processed to evaluate body injuries and breast meat quality. Increasing stocking densities decreased feathering and increased body injuries like breast blisters, dermatitis, bruises and scratches. Breast meat yield and breast length width and depth was negatively affected (p<.05) as stocking densities increased.
Effect of stocking density and sex on feathering, body injury and breast meat quality of broiler chikens
Keywords: Body injuries; Breast meat quality; Broiler chickens; Feathering; Stocking densities